Optimization of quality of service parameters for efficient channel allocation - Saxena, Aditya; Singhai, Jyoti; Raghuvanshi, Deepak (International Journal of Engineering and Technology, 2018)
The bandwidth-intensive network applications with aggressive quality of service (QoS) requirements requires fast and efficient networks. The wireless network performance is impacted due to multitude of data transport at uneven transmission rates on various channels and line losses leading to congestion. It is a big challenge to achieve the required QoS by managing delay, jitter, bandwidth and packet loss parame-ters on a network. This paper highlights the major causes affecting QoS and proposes an optimization technique which allocates the channel dynamically by integrating all the parameters affecting QoS across network layer, medium access control (MAC) layer and physical layer. The proposed algorithm utilizes the feedback parameters namely queueing delay, packet priority and timeout, MAC layer contention delay and packet loss ratio as inputs and a closed loop processing control for the scheduler based on fuzzy logic control (FLC). Hence, the algo-rithm is more realistic and considers the line conditions. The simulation results show that the proposed algorithm is faster and utilizes the overall network more efficiently.Â Â Â